The summer I turned pretty trilogy - Han, Jenny (New York : Penguin Books, 2022)
Belly spends the summer she turns sixteen at the beach just like every other summer of her life, but this time things are very different.
Keywords: Beaches -- Fiction; Friendship -- Fiction; Interpersonal relations -- Fiction